The influence of cooperative relations of small businesses on environmental protection intensity. (21st June 2016) - Benito‐Hernández, Sonia; Platero‐Jaime, Manuel; Esteban-Sánchez, Pablo
Abstract : This study examines the relationship between cooperative business relations in small businesses (fewer than 50 employees) and environmental protection, one of the most important policies of social responsibility in manufacturing. We reviewed the literature and carried out an empirical study of 930 small manufacturing firms in Spain. Results indicate that small businesses that maintain and improve their cooperative relations through business networking with universities, competitors, suppliers and customers spend more on environmental protection. The managerial, practical, research and policy implications of the obtained research findings are discussed.